A logic programming approach for the conservation of buildings based on an extension of the Eindhoven Classification Model - Gomes, Guida (2013)
The identification, classification and recording of events that may lead to the deterioration of buildings are crucial for the development of appropriate repair strategies. This work presents an extension of the Eindhoven Classification Model to sort adverse events root causes for Building Conservation. Logic Programming was used for knowledge representation and reasoning, letting the modelling of the universe of discourse in terms of defective data, information and knowledge. Indeed, a systematization of the evolution process of the body of knowledge in terms of a new factor, the Quality of Information one, embedded in the Root Cause Analysis was accomplished, i.e., the system proposed led to a process of Quality of Information quantification that permit the study of the event's root causes, on time.